A Gold Needle Tip Array Ultrafast Electron Source with High Beam Quality - Brückner, Leon; Nauk, Constantin; Dienstbier, Philip; Gerner, Constanze; Löhrl, Bastian; Paschen, Timo; Hommelhoff, Peter (2024 37th International Vacuum Nanoelectronics Conference (IVNC), 2024)
Nanometer-sharp needle tips are the electron sources with the highest beam quality. However, for a single needle tip, the total emission current is limited. Combining multiple needles into an array of tips should allow for higher currents while preserving the properties of the individual emitters. Previous studies on tip arrays have shown impressive emission character-istics, but could not demonstrate favourable transversal beam properties such as a well-behaved spot shape or low emittance. Here, we introduce an ultrafast electron source composed of a lithographically fabricated array of nanometer-sharp gold tips illuminated by 25 fs laser pulses. By harnessing the emission of multiple needles, we achieve a high-current electron beam while preserving individual emitter properties. Our source delivers up to 2000 electrons per pulse at moderate laser peak intensities of 10 11 w /cm 2 , with a narrow energy width of 0.5 ± 0.05 eV and a well-behaved Gaussian profile. The resulting electron beam exhibits high collimation and a small normalized emittance on the order of nm.rad, making it ideal for applications requiring both high current and spatial resolution, such as free-electron light sources and chip-based particle accelerator

A Gold Needle Tip Array Ultrafast Electron Source with High Beam Quality - Brückner, Leon; Nauk, Constantin; Dienstbier, Philip; Gerner, Constanze; Löhrl, Bastian; Paschen, Timo; Hommelhoff, Peter (Nano Letters, 2024)
Electron sources are crucial elements in diverse applications such as electron microscopes, synchrotrons, and free-electron lasers. Nanometer-sharp needle tips are electron emitters with the highest beam quality, yet for a single needle the current is limited. Combining the emission of multiple needles promises large current yields while preserving the individual emitters’ favorable properties. We present an ultrafast electron source consisting of a lithographically fabricated array of sharp gold tips illuminated with 25 fs laser pulses. The source provides up to 2000 electrons per pulse for moderate laser peak intensities of 1011 W/cm2 and a narrow energy width of 0.5 ± 0.05 eV at low current. The electron beam has a well-behaved Gaussian profile and is highly collimated, yielding a small normalized emittance on the order of nm·rad. These properties are well suited for applications requiring both high current and spatial resolution, such as free-electron light sources and chip-based particle accelerators.<br
Keywords: nano-optics; ultrafast electron emission; field enhancement; lasers; electron sources

Strong-field spectra and optical near-field enhancement at aluminium needle tips - Paschen, Timo; Nauk, Constantin; Dienstbier, Philip; Hommelhoff, Peter (Journal of Physics B: Atomic, Molecular and Optical Physics, 2021)
We study the rescattering of photoemitted electrons at aluminium needle tips. For various laser intensities we measure electron energy spectra to identify telltale features of strong-field rescattering, in particular a plateau with near-constant count rate and a high-energy cutoff. This rescattering process is used to investigate the geometry-dependent enhanced optical near-field at the apex of the aluminium tip. A large near-field enhancement, extracted from the spectral data, is supported by 3D finite-difference time-domain simulations. A systematic theoretical investigation of the near-field enhancement at aluminium tips shows a strong dependence on tip opening angle and radius of curvatur
Keywords: electron sources; aluminium needle tips; strong-field physics; rescattering; optical near-fields